2022
DOI: 10.36456/waktu.v20i02.6044
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Bod, Cod Dan TSS Pada Limbah Domestik Menggunakan Kombinasi Floating Wetland Dilanjutkan Constructed Wetland

Abstract: Seiring laju perkembangan penduduk di Indonesia yang semakin meningkat tiap tahunnya, meningkat pula jumlah kebutuhan air bersih yang digunakan mengakibatkan volume air limbah yang dihasilkan cukup melimpah terutama di perkotaan salah satunya adalah limbah domestik. Limbah domestik mengandung bahan organik dan anorganik maupun gas yang terkandung dalam limbah cair rumah tangga dapat mencemari lingkungan serta menyebabkan berbagai penyakit. Limbah cair yang dihasilkan biasanya memiliki nilai konsentrasi Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the RK reactor, the efficiency of reducing BOD levels in the leachate was 29%. Hadi and Pungut [25], revealed that the efficiency of reducing BOD levels in leachate using Constructed Wetland with Echinodorus paleafolius was 61%. An efficiency of reducing BOD in leachate using constructed wetlands with Typha angustifolia plants by 30.9-98.8% [16,18].…”
Section: Reduction Of Bod Levels In Leachatementioning
confidence: 99%
See 1 more Smart Citation
“…In the RK reactor, the efficiency of reducing BOD levels in the leachate was 29%. Hadi and Pungut [25], revealed that the efficiency of reducing BOD levels in leachate using Constructed Wetland with Echinodorus paleafolius was 61%. An efficiency of reducing BOD in leachate using constructed wetlands with Typha angustifolia plants by 30.9-98.8% [16,18].…”
Section: Reduction Of Bod Levels In Leachatementioning
confidence: 99%
“…This reduction results from the sedimentation process in R1 reactor, where organic particles settle and undergo gravitational sedimentation. Typically, 60% of the suspended particles in wastewater consist of sedimented elements [25,26]. Therefore, it can be said that the control reactor, which has no treatment, can reduce the COD levels of the leachate owing to the sedimentation of organic particles in the reactor.…”
Section: Reduction Of Cod Levels In Leachatementioning
confidence: 99%
“…Jaringan akar akan berpengaruh pada penurunan COD, jika semakin dalam jaringan akar tersebut maka zona rhizosfer yang tercipta akan semakin luas juga. Sesuai dengan bentuk akar pada melati air dimana akar melati air yang kuat dan menjalar yang berfungsi sebagai tempat melekatnya mikroorganisme (Hadi & Pungut, 2022). Pada penelitian ini, debit dan waktu sampling memengaruhi penurunan COD, semakin lama waktu sampling akan semakin meningkat persentase penyisihan COD dan semakin kecil debit yang masuk maka semakin meningkat persentase penyisihan COD.…”
Section: Penurunan Cod Pada Melati Airunclassified
“…The highest reduction in COD in water jasmine plants is because the root tissue is very influential, where the deeper the root tissue, the wider the rhizosphere zone is created. Water jasmine also has long, spreading roots which cause more microorganisms to stick to the roots so that the microorganisms can degrade more pollutants (Hadi & Pungut, 2022). Another characteristic of water jasmine roots is that the roots of water jasmine have holes so they can release organic substances as food for microorganisms which causes strong biological activity.…”
Section: Reduction Cod In Water Jasmine and Spider Plantmentioning
confidence: 99%